METHODOLOGY OF FORMATION OF CREATIVE COMPETENCE OF STUDENTS IN THE EDUCATIONAL PROCESS USING THE RESOURCES OF PEDAGOGICAL TECHNOLOGIES - Almardanova Rohila Choriyevna (Journals Park Publishing, 2022)
The choice of an innovative way of development, the creation and implementation of high technologies, the growing role of knowledge and information in the socio-economic development of the country places a great demand on highly qualified specialists. This article describes the creative competence of future teachers. the test results of development, personal creativity qualities, factors, ways of developing creative competence, and methods and strategies of creative teaching are highlighted. The article talks about the methodology of forming the creative competence of students in the educational process using the resources of pedagogical technologies goes.
Keywords: methodology, creative competence, creativity, education, pedagogy, technology, society.